Aerodynamic Performance Enhancement of Electric Vehicles Using Selig 1223 Airfoil Wing-Type Spoiler: A Computational Fluid Dynamics Study - Fajar Rizqi Sandi Pratama; Aldias Bahatmaka; Amin, Muklis; Hyung, Cho Joung (Universitas Negeri Semarang, 2024)
The performance of electric vehicles (EVs) is significantly influenced by aerodynamic forces, which directly affect energy consumption and vehicle stability. One of the main challenges in this regard is the increase in lift and drag forces at higher speeds, which compromises efficiency and handling. This study investigates the impact of a wing type rear spoiler, designed using the Selig 1223 airfoil, on the aerodynamic behavior of EVs. A comparative computational fluid dynamics (CFD) simulation was conducted on two vehicle models: one without a spoiler and another equipped with the Selig 1223 spoiler mounted at a 15° angle of attack. Both models were tested under five speed conditions ranging from 40 to 120 km/h. The simulation results demonstrated a notable improvement in aerodynamic performance. The spoiler produced an average reduction in the lift coefficient (Cl) of approximately 110%, while the drag coefficient (Cd) showed only a slight increase, with the highest recorded rise being 13.3% at 120 km/h. Pressure distribution analysis revealed a substantial increase in static pressure at the rear of the vehicle (Point P3), rising from 37.47 Pa to 660.859 Pa, indicating enhanced downforce. Additionally, streamline and velocity contour plots confirmed improved airflow regulation and reduced turbulence behind the vehicle when the spoiler was installed. These findings indicate that the Selig 1223 airfoil spoiler effectively enhances EV stability and safety with minimal aerodynamic penalties, making it a promising aerodynamic enhancement for future electric vehicle designs.